Activation of the prelimbic medial prefrontal cortex induces anxiety‐like behaviors via N‐Methyl‐D‐aspartate receptor‐mediated glutamatergic neurotransmission in mice. Issue 8 (21st April 2014) - Saitoh, Akiyoshi; Ohashi, Masanori; Suzuki, Satoshi; Tsukagoshi, Mai; Sugiyama, Azusa; Yamada, Misa; Oka, Jun‐Ichiro; Inagaki, Masatoshi; Yamada, Mitsuhiko
<x xml:space="preserve">Abstract</x> We investigated the possible roles of the prelimbic medial prefrontal cortex (PL) in the regulation of anxiety‐like behaviors by pharmacologically activating the terminals of neuronal inputs or postsynaptic efferent neurons with a sodium channel activator veratrine. The extracellular glutamate levels were measured by in vivo microdialysis, and the behaviors were assessed with the open field (OF) test in mice simultaneously. The samples were collected every 10 min for 60 min, as basal levels of glutamate. The medium containing drugs were perfused for 30 min. The OF test was performed in the last 10 min of drug perfusion. After the drug treatments, the perfusion medium containing drugs was switched back to perfusion medium without drugs, and then samples were collected for another 90 min. The extracellular glutamate levels were significantly elevated after local perfusion of veratrine in the PL. At the same time, perfusion of veratrine in the PL produced anxiety‐like behaviors in mice. Local coperfusion of a sodium channel blocker, lamotrigine, completely diminished the veratrine‐induced elevated extracellular glutamate levels and the behavioral changes. Local coperfusion of an NMDA receptor antagonist, MK‐801, but not a non‐NMDA (AMPA/kainate) receptor antagonist, CNQX, completely diminished the behavioral changes without any effects on the veratrine‐induced elevated extracellular glutamate levels. This study demonstrates that the activation of the PL with veratrine induces anxiety‐like behaviors via NMDA receptor‐mediated glutamatergic neurotransmission in mice. © 2014 Wiley Periodicals, Inc.